Log smoldering after an Amazonian deforestation fire - Rabelo, ERC; Veras, CAG; Carvalho, J. A.; Alvarado, E. C.; Sandberg, D. V.; Santos, J. C. (Elsevier B.V., 2004)
The characteristics of log smoldering after an Amazonian deforestation fire are described. The experiment was carried out in 2001 at the Caiabi farm, near the city of Alta Floresta, state of Mato Grosso, Brazil, as part of a set of tests that have been performed in the same area since 1997. A 200 x 200m(2) test area was slashed in the beginning of June and burned on 20 August. The area contained 507 logs with diameter at breast height (DBH) higher than 10 cm, per hectare. In the day following the main burn 59 logs were found to remain smoldering, a number that corresponds to 2.9% of the total in the area. We chose 11 of the 59 logs to have their smoldering process monitored. Their diameter, moisture content and CHN dry biomass composition after the plot burn and before smoldering were determined. Other parameters such as temperature distribution while smoldering, porosity, density and mass volatilized during thermogravimetric test were also determined. Average smoldering speeds were in the range from 0.8 to 1.5 cm h(-1) for logs that smoldered without transition to the flaming regime. The average speed increased to 2.1 cm h(-1) for those logs that oscillated between smoldering and flaming. The speeds were lower overnight as compared to values determined during daytime for the same log. Higher log moisture contents were found to produce decreased speeds. Micro-porous biomass was not observed in the set of the 11 selected logs. Smoldering was observed to occur at substantial intensity in crossing of logs, with no longitudinal propagation. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: smoldering; biomass combustion; deforestation fire